The Role of South Korea in Nuclear Crisis on the Korean Peninsula in 2000–2018 - Limyingcharoen, Budsayapan (Thai Journal of East Asian Studies, 2019)
Since the 2000s, North Korea’s Nuclear weapons and ballistic missiles have increased in number and efficiency. South Korea, which is a neighboring country that North Korea may attack first, must find a way to cope and solve the nuclear problems. In 1998, South Korea announced the Engagement Policy to improve inter-Korean Relations and solve the nuclear problems. Then, the Engagement Policy became a constant theme in South Korea’s policy to North Korea for two decades. However, the policy has not been implemented smoothly because each president prioritized the policy differently depends on their political ideology. The progressive presidents have inclined to support and focus on the engagement policy more than the conservative presidents, which prefer aggressive means. In addition, South Korea still needs the influence and policy of the United States, as a superpower and main party, to support South Korea’s policy to tackle the nuclear problems.